Developing age-oriented design framework with technology acceptance model for smart appliances to improve technology acceptance by ageing community in Guangzhou China - Che Me, Rosalam; Jinglong, Li; Qisen, Zhu (Human Resource Management Academic Research Society, 2024)
With the growing ageing community and the rapid development of smart appliances, the acceptance of smart appliances among the ageing community presents a critical challenge in the face of demographic shift and rapid technological improvement. This research seeks to address the pressing need for understanding and improving the acceptance of smart appliances among the ageing community, given the profound societal implications of facilitating their integration into daily life amidst demographic changes and technological advancements. As a result, improving the design of smart appliances is necessary to increase acceptance among the elderly population. This study adopted a literature review method to investigate the characteristics and design elements of smart appliances tailored to the needs of elderly users, providing insights into elderly smart appliance design. Results identified significant behavioural and psychological characteristics among the elderly. Through comprehensive analysis, it was revealed that variables such as familiarity with technology, perceived usefulness, ease of use, and trust in the reliability of smart appliances strongly influence technology acceptance among the ageing community. Moreover, the study elucidated specific preferences and concerns of elderly users, including the importance of clear interfaces, simplified controls, and compatibility with existing routines and habits. These findings underscore the importance of tailoring smart appliance designs to accommodate the unique needs of elderly users, ultimately enhancing their technology acceptance. By providing a framework for age-oriented appliance design, this research endeavours to facilitate the seamless integration of smart technologies into the lives of elderly individuals, enhancing their independence, safety, and overall well-being through the thoughtful design and implementation of smart appliances tailored to their specific needs and preferences.